Validity of an Assessment Instrument for Measuring Students’ Eco-‎Awareness of Sidoarjo’s Traditional Aquaculture Pond Ecosystem - Endy Sri Wigati; Wisanti; Raharjo (Yayasan Darussalam Bengkulu, 2026)
This study aimed to develop and obtain preliminary validation evidence for an essay-based instrument assessing senior high school students’ eco-awareness ecological knowledge, attitudes, and behavior through the local context of Sidoarjo’s traditional aquatic pond ecosystem. Using a research and development design adapted from the MEASURE approach, the study included blueprint preparation, item construction, expert validation, revision, pilot testing, and psychometric analysis. The initial instrument comprised seven essay items reviewed by four validators: two university lecturers and two senior high school biology teachers. Pilot testing involved 30 Grade 11 students who had studied ecosystem concepts and were excluded from the main sample. Content validity was evaluated through expert-rating percentages, empirical validity through Pearson item–total correlations, and internal consistency through Cronbach’s alpha. Expert-validation scores ranged from 97.92% to 100%, indicating very high content relevance, construction quality, and linguistic clarity. Six items showed significant item–total correlations ranging from .484 to .774, while one item failed to meet the empirical-validity criterion (r = .092, p = .629) and required revision or removal. The six retained items yielded a Cronbach’s alpha of .656, indicating acceptable preliminary consistency for formative use. These findings suggest that the instrument can support contextual assessment of students’ environmental reasoning and assist biology teachers in diagnosing eco-awareness through locally grounded ecological learning. However, the small pilot sample and limited item pool restrict generalizability; further testing with larger, more diverse samples and broader validity evidence is required before high-stakes use.